2000
DOI: 10.1046/j.1365-3148.2000.00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting a donor's likelihood of donating within a preselected time interval

Abstract: The procurement of some advanced blood components, like quarantined plasma units, depends critically on retesting the donor within a fixed time frame. For health care systems, such as that in Germany, with mandatory retesting of donors before plasma release, the reliable identification of donors who are more likely to return in time has an immense practical implication, because their blood components could be preferably selected for quarantine purposes. The donation histories of about 760 000 donors with 4910 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 13 publications
4
22
0
1
Order By: Relevance
“…This is consistent with the data of James and Matthews 5 who found that the proportion of returning donors increased with the donors’ number of previous donation attempts. It is also consistent with the prediction model of Flegel and colleagues, 6 which used a score function based on the donor's response to previous opportunities to donate as the main explanatory variable. A high number of donations during the preceding 2 years would be expected to result in a higher value of this score function.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…This is consistent with the data of James and Matthews 5 who found that the proportion of returning donors increased with the donors’ number of previous donation attempts. It is also consistent with the prediction model of Flegel and colleagues, 6 which used a score function based on the donor's response to previous opportunities to donate as the main explanatory variable. A high number of donations during the preceding 2 years would be expected to result in a higher value of this score function.…”
Section: Discussionsupporting
confidence: 84%
“…Eighteen explanatory variables were selected. The choice of variables was based on previous reports on blood donor return behavior, 4‐8 as well as on the accessibility of the data and our assumptions about their potential predictive value. The explanatory variables are listed in Table 1, with summary statistics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Male sex was also a significant predictor of frequent blood donation in the present study, together with the higher attitude score to donation. Experience of prior blood donation, number of previous donations, and duration from last donation are correlated with future behavior 40–42. Individual attachment with someone who donates blood, or knowing people who have received donated blood all could influence willingness to donate blood 30,43,44.…”
Section: Discussionmentioning
confidence: 99%